2021
DOI: 10.3389/fgene.2021.636550
|View full text |Cite|
|
Sign up to set email alerts
|

Bovine Pre-adipocyte Adipogenesis Is Regulated by bta-miR-150 Through mTOR Signaling

Abstract: Micro RNA (miR) are recognized for their important roles in biological processes, particularly in regulatory componentization. Among the miR, miR-150 has been the focus of intense scrutiny, mostly due to its role in malignant tumors. A comparison between steer and bull adipose tissues identified bta-miR-150 as one of the nine downregulated miRNAs, although its function remains unknown (GEO:GSE75063). The present study aimed to further characterize the role of bta-miR-150 in cattle. bta-miR-150 has a negative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…This means that many previous studies focusing on humans and mice have lost their original reference value in the field of livestock production. Additionally, most studies on animal adipogenesis have focused on subcutaneous and perirenal fat [13,[15][16][17][18][19][20][21], with fewer studies on intramuscular adipose tissue. The origin and development of IMF are different from that of other adipose tissues, which makes it impossible to fully replicate the studies of other adipose tissues in IMF tissue as well [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that many previous studies focusing on humans and mice have lost their original reference value in the field of livestock production. Additionally, most studies on animal adipogenesis have focused on subcutaneous and perirenal fat [13,[15][16][17][18][19][20][21], with fewer studies on intramuscular adipose tissue. The origin and development of IMF are different from that of other adipose tissues, which makes it impossible to fully replicate the studies of other adipose tissues in IMF tissue as well [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…miR-NAs are strongly and functionally conserved among species and were the first noncoding RNAs identified and characterized [14]. Our previous studies have shown that bta-miR-150 regulates the mTOR pathway by targeting the 3'UTR of AKT1, thereby affecting the proliferation and differentiation of bovine preadipocytes [15]. bta-miR-376a inhibited bovine adipocyte differentiation through the KLF15/PPARG axis [16].…”
Section: Introductionmentioning
confidence: 99%
“…The results were expressed as mean ± standard error of the mean (SEM). Statistical analyzes were performed with SPSS 25 (37) and Graphpad Prism 9 (38). Differences between groups were * p < 0.05, significant; * * p < 0.01, moderately significant; * * * p < 0.001, highly significant; and * * * * p < 0.0001, extremely significant.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that three biological replicates and technical replicates were performed for all experiments. SPSS 25 ( 37 ) and Graphpad Prism 9 ( 38 ) softwares were used for difference significance analysis and mapping, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation